2011
DOI: 10.1007/978-1-60761-999-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Human Mesenchymal Stem Cells Differentiating into Chondrogenic, Osteogenic, and Adipogenic Lineages

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that have the potential to differentiate into various mesenchymal lineages in vitro and in vivo. Due to their availability from tissues such as bone marrow, synovium, fat, and muscle, and their highly proliferative capacity, MSCs have evoked interest as a potential cell source for repair and regeneration of various types of tissues. Characterization by the expression of a panel of surface markers and the ability of MSCs to undergo multilineage differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…We found that after treatment with either IL6, IL8 or both differentiation induction into mesenchymal lineages occurred remarkably fast (10 days compared to the 2–3 weeks needed for the differentiation of bone-marrow mesenchymal stem cells [61, 62]), and very efficiently (as judged by the intense and more homogenous staining in the culture dish) (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…We found that after treatment with either IL6, IL8 or both differentiation induction into mesenchymal lineages occurred remarkably fast (10 days compared to the 2–3 weeks needed for the differentiation of bone-marrow mesenchymal stem cells [61, 62]), and very efficiently (as judged by the intense and more homogenous staining in the culture dish) (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were seeded onto modified and unmodified hydrogels as described above. After incubation for 24 h in growth medium, cells were cultured for 21 days in osteogenic (DMEM with 10% FBS, 1 mM sodium pyruvate (Life Technologies), 100 U/100 μg penicillin–streptomycin, 10 –7 M dexamethasone (Sigma-Aldrich), 50 μg/mL ascorbic acid (Sigma-Aldrich), and 10 mM β-glycerophosphate), chondrogenic (high glucose DMEM supplemented with ITS (BD, Franklin Lakes, NJ), 4 mM l -proline (Sigma-Aldrich), 50 μg/mL ascorbic acid, 1% sodium pyruvate, 10 –7 M dexamethasone, and 100 U/100 μg penicillin–streptomycin, and 10 ng/μL TGF-β3 (R&D Systems, Minneapolis, MN)), or adipogenic (DMEM with 10% FBS, 1 mM sodium pyruvate, 100 U/100 μg penicillin–streptomycin, 10 –6 M dexamethasone, 10 μg/mL insulin (Sigma-Aldrich), 0.5 mM IBMX (Life Technologies), and 200 μM indomethacin (Life Technologies)) media as described by Yang et al 26 Growth media as well as groups cultured on TCPS were used as controls. All media were changed every 3 days.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Optimizing these microenvironmental cues is of particular interest in regenerative medicine where biomaterial substrates may serve as a vehicle for directed cell delivery or as a system for tissue formation in-vivo . Commonly used methods for assessing microenironment modulated osteogenic and adipogenic differentiation include reverse transcriptase PCR (RT-PCR) for detection of osteogenic or adipogenic transcripts, immunohistochemical analysis, enzyme linked immunosorbent assay (ELISA) or western blotting for secreted protein markers, colorimetric assays, and direct staining of matrix components 8, 9 . To aid in identifying optimal microenvironments that efficiently elicit strategic stem cell phenotypes, high-throughput screening (HTS) approaches that allow for the assessment of up to several thousand conditions within one experiment have also been developed 1012 .…”
Section: Introductionmentioning
confidence: 99%